Determinants of Syariah Financial Inclusion: a Case Study of Riau Province - Zainal Arifin (Budapest International Research and Critics University, 2022)
The purpose of this research is to find out and analyze determinants of syariah financial Inclusion for a case study of Riau Province. This type of research is descriptive quantitative. The data used is secondary data. The analytical method used in this research is multiple linear regression. Based on the results of the study, it shows that the Riau Province of index of syariah financial inclusion can be categorized in the medium. Economic growth and human development index have significant effect on index of syariah financial inclusion, while the gini ratio has no significant effect on index of syariah financial inclusion.